Regulatory Takings and Evasion of Compensation Requirement through Overlapping Regulations - Hojun Lee (Korea Development Institute (KDI), 2016)
The public's awareness of property rights has improved significantly, and judicial authorities, including the Constitutional Court, more frequently rule in favor of property rights protection than ever before. Accordingly, it has become vital that a shift be made with regards to conventional perceptions of property rights protection and compensation, and existing systems are reformed in the process of adopting or upgrading regulations. - Korea lacks definitive criteria that define justifiable state limitations on property rights and compensation and instead, relies on the discretion of those who hold administrative authority. - The two representative criterions to determine whether to compensate for loss are (1) wellrecognized right before infringement and (2) disproportionality. - Representative regulatory takings that call for proper compensation include regulations on development restriction zones and development activity in areas designated for urban planning facilities. - Despite the Constitutional Court's decision in favor of compensation for the loss incurred via the regulations on development restriction zones and longprotracted projects for urban planning facilities, local authorities have sought to adopt additional regulations in order to evade paying compensation. - Potentially overlapping regulations need to be overhauled, and regulations that may inflict severe damage to property rights must be based on the law, not on local ordinance. Also, sincere consideration should be given to adopting rules to provide just compensation for the loss incurred.
Keywords: 330